Insights into the nutritional properties and molecular basis of biosynthesis of amino acids and vitamins of Gastrodia elata offered by metabolomic and transcriptomic analysis - Wang, Yunsheng; Shahid, Muhammad Qasim (Frontiers in Plant Science, 2023)
Gastrodia elata Blume (GE), a traditional and precious Chinese medicinal material, has been approved as a functional food. However, understanding GE's nutritional properties and its molecular basis remains limited. Here, metabolomic and transcriptomic analyses were per-formed on young and mature tubers of G. elata.f.elata (GEEy and GEEm) and G. ela-ta.f.glauca (GEGy and GEGm). A total of 345 metabolites were detected, including 76 dif-ferent amino acids and their derivatives containing all human essential amino acids (e.g., l-(+)-lysine, l-leucine), 13 vitamins (e.g., nicotinamide, thiamine), and 34 alkaloids (e.g., spermine, choline). GEGm has higher amino acid accumulation than GEEy, GEEm and GEGy, and vitamin contents were also slightly different in all four samples. Implying that GE, especially GEGm, is a kind of excellent complementary food as amino acid nutrition provider. From assembled 21,513 transcripts (genes) based on the transcriptome, we identified many genes that encode enzymes (e.g., pfkA, bglX, tyrAa, lysA, his B, aroA), which are responsible for the biosynthesis of amino acids and enzymes (e.g., nadA, URH1, NAPRT1, punA, rsgA) that related to vitamins metabolism. A total of 16 pairs of the differentially expressed genes (DEG) and differentially accumulated metabolites (DAM) (e.g., gene-tia006709 coding GAPDH and l-(+)-arginine, and gene-tia010180 coding tyrA and l-(+)-arginine) and three DEG-DAM pairs (e.g., gene-tia015379 coding NadA and nicotinate d-ribonucleoside) show significant similar positive or negative correlation based on three, and two comparisons of GEEy vs GEGy, GEGy vs GEGm, GEEy vs GEGy and GEEm vs GEGm, which involved into amino acid biosynthesis, and nicotinate nicotinamide metabolism, respectively. These re-sults prove that the enzyme coded by these DEG promotes (positive correlation) or inhibits (negative correlation) the biosynthesis of parallel DAM in GE. Overall, the data and corre-sponding analysis in this study provide new insights into the nutritional properties of GE and the related molecular basis.